Stylosanthes accessions for medium-altitude acid soils - Larbi, Asamoah; Hanson, Jean; Ochang, J. (International Livestock Centre for Africa, 1994)
Thirty-four Stylosanthes scabra, 20 S. guianensis and 66 S. hamata accessions were compared for biomass production on an acid soil in a medium-altitude subhumid environment in southern Ethiopia. Accessions S. scabra (ILCA 12555, 11625, 11599 and 11608), S. guianensis (ILCA 11737 and 11776) and S. hamata (ILCA 167) outyielded existing commercial cultivars and are recommended for further agronomic evaluation and animal feed trials in similar environments in sub-Saharan Africa.